Synthesis of 4-Vinyl-1,2,3,4-tetrahydroisoquinoline from N-Tethered Benzyl-Alkenol Catalyzed by Indium(III) Chloride: Formal Synthesis of (±)-Isocyclocelabenzine - Devi, Ngangbam Renubala; Shit, Sudip; Behera, Bipin Kumar; Saikia, Anil K. (Synthesis, 2020)
An intramolecular Friedel–Crafts cyclization reaction catalyzed by indium(III) chloride for the formation of 4-vinyl-1,2,3,4-tetrahydroisoquinoline from N-tethered benzyl-alkenol in good yields has been described. The reaction is highly regioselective and generates an exocyclic vinyl functionality in the piperidine ring. The reaction is compatible with a wide range of functional groups. The strategy is demonstrated for the formal synthesis of (±)-isocyclocelabenzine alkaloid.
Keywords: tetrahydroisoquinoline; (±)-isocyclocelabenzine; indium(III) chloride; regioselectivity; N-tethered benzyl-alkenol; Friedel–Crafts